The role of inflammation in cardiac arrhythmias pathophysiology - Budzianowski, Jan Krzysztof; Korybalska, Katarzyna; Bręborowicz, Andrzej (Journal of Medical Science, 2016)
The pathophysiology of cardiac arrhythmias is highly complex. Inflammation causes electrophysiological changes that contribute to increased vulnerability of arrhythmias, a process known as electrical remodeling. There have been many biomarkers and proteins associated with pathophysiology of cardiac arrhythmias such as C-reactive protein, tumor necrosis factor-?, interleukin-2, interleukin-6, interleukin-8, and monocyte chemoattractant protein-1. At present large attention is paid to the clinical studies on the inflammation in the pathogenesis of the atrial fibrillation (AF), given the limited effectiveness of the current therapeutic approaches. Understanding the main process, molecular mechanism and signaling pathways underlying the pathogenesis of the inflammatory dilated cardiomyopathy (iDCM) will be essential for developing new effective therapeutic strategies.
Keywords: inflammation; atrial fibrillation; biomarkers; remodeling